The Nature of the Il17 Cytokine Response In Rabbits PrimeBoosted With Eschrchia Coli-Pseudomonas Aeruginosa Prototype Bacterin Combinations (Medico Legal Update, 2020)
The prototype E .coli - P. aeruginosa heat killed bacterin balanced and unbalanced bacterin combinations,aswell as monotypic E. coli and single P. aeruginosa bacterins were developed. They were prime-boostedrabbits by homologous prime-boost protocols. At the end of the specific immune-priming protocols ,rabbitswere bleed, sera saved in 0.5 ml aliquots at -18C till testing due time.IL17 Eliza assay was done on the testand control sera. Single strength balanced combined bacterin combination induced increase in the meanIL17 concentration means as compared to monotypic, double balanced ,un-balanced bcterin combinationsand control. The other combinations were showing inhibition in IL17 concentration means than control .Theimmune interference matched To as: one bacterin enhance the other, and one damp the other. Enhancement ofIL17 response single strength combination might be a promise for efficacy of such combination in regulationand protection against natural or experimental infectious challenges .